Is Condom Use Safe? Youth Perceptions on the Use of Condoms In Muleba, Handeni and Ludewa Districts, Tanzania - Ndaluka, Thomas (Tanzania Journal for Population studies and Development, 2014)
This article attempts to explain youth perceptions on condom use. For more than thirty years since the onset of HIV/AIDS in Tanzania, condom is still regarded as one of the three preventive measures against HIV infection. The other two are abstinence and faithfulness to one un-infected partner, referred shortly as ABC. Available evidence shows that despite continued efforts to campaign for condom use during sexual intercourse, its use has been low. The article addresses this mismatch between the rate of awareness and knowledge about HIV and low rate of condom use among the youth, and how youth perceptions leads to this discrepancy. This article used data collected between 2007 and 2008 through survey questionnaire and focus group discussions (FGDs) in three districts of Muleba, Handeni and Ludewa districts. The finding shows that youth’s awareness and knowledge on HIV/AIDS and how one gets infected with the virus was high, to about 91%. Awareness on where to obtain condoms was 76%. However, despite this high rate of awareness the use of condom by youth was low, to about 33%: Ludewa recorded the lowest rate of (7%), followed by Muleba (12%), and Handeni (14%). The discrepancy was attributed to youth perceptions on the ability of condom to protect against HIV infection. Most youth do not use condom during sex and treat condom with suspicion. The article recommends an increased campaign on the use of condom, focusing on this category of the population and addressing cultural challenges on issues related to sex that youth are subjected to.